Opportunity for Optimising a Common Rail Engine Using Palm Oil Biodiesel - Abdullah, M Adlan; Ani, Farid Nasir; Hassan, Masjuki (International Journal of Engineering and Technology, 2018)
emission while producing significantly low black smoke. This is due to the inherent chemical and physical properties of biodiesel which results in un-optimised engine operating parameters. This paper presents the investigation on the potential of optimizing common rail diesel engine for palm oil biodiesel. Low to medium speed and the load was chosen for this optimization due to the significant changes in performance and emission when operating with palm oil biodiesel. Fuel injection and rail pressure sweep were conducted at 2000 rpm and 3000 rpm for biodiesel blends of 10%, 20% and 30%. The smoke and NOx emissions, as well as the fuel consumption, were recorded. The results were compared to nominal fuel injection parameter settings with the aim to improve the fuel economy while keeping the smoke and NOx emissions to within original diesel values. The results indicated that the Brake Specific Fuel Consumption(BSFC) remains relatively constant at a fixed end of injection (EOI) regardless of the rail pressure. NOx and smoke emissions varied significantly with both EOI and rail pressure. It was also shown that the optimum parameter settings for biodiesel were at lower rail pressure and at nominal end of injection, where the emissions were kept to original diesel values and the fuel consumption was reduced.